2010
DOI: 10.1002/bit.22650
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the hydrostatic pressure and pH on the asymmetric 2‐hydroxyketone formation catalyzed by Pseudomonas putida benzoylformate decarboxylase and variants thereof

Abstract: Benzoylformate decarboxylase (BFD) from Pseudomonas putida is a thiamine diphosphate-dependent (ThDP) enzyme that catalyzes the asymmetric C--C bond formation to (S)-2-hydroxypropiophenone [(S)-HPP] starting from benzaldehyde and acetaldehyde. The enantioselectivity of BFD was shown to be a function of temperature and substrate concentration. It can additionally be changed by site-directed mutagenesis on hot spot positions in the active site. In this article, we present the effect of hydrostatic pressure up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 69 publications
0
23
0
Order By: Relevance
“…Influence of pressure on the enantioselectivity of the immobilized enzyme A significant pressure effect on the enantioselectivity of the BFD A460I-F464I variant was found in previous investigations. With increasing pressure, a general tendency towards higher amounts of (R)-2-HPP could be observed [20]. While the previous investigations were done with free enzyme, in this work the influence of pressure on the enantioselectivity of the carrier bound enzyme was investigated.…”
Section: Stability Of the Silica-immobilized Bfd A460i-f464i And Kinementioning
confidence: 96%
See 2 more Smart Citations
“…Influence of pressure on the enantioselectivity of the immobilized enzyme A significant pressure effect on the enantioselectivity of the BFD A460I-F464I variant was found in previous investigations. With increasing pressure, a general tendency towards higher amounts of (R)-2-HPP could be observed [20]. While the previous investigations were done with free enzyme, in this work the influence of pressure on the enantioselectivity of the carrier bound enzyme was investigated.…”
Section: Stability Of the Silica-immobilized Bfd A460i-f464i And Kinementioning
confidence: 96%
“…Furthermore, a change of selectivity can be the result of steric effects through pressure-induced structural changes. In previous investigations, we found a significant pressure effect on the enantioselectivity of the BFD A460I-F464I variant [20]. Whereas the previous investigations were done with free enzyme, in this work the influence of pressure on the enantioselectivity of the carrier-bound enzyme was investigated.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In Berheide et al (2010) we have recently demonstrated that hydrostatic pressure and pH are important factors to influence the enantioselectivity of BFD-catalyzed C-C bond formation yielding 2-HPP. As a general trend we observed an increase in (R)-2-HPP synthesis, consequently a decrease in the ee of (S)-2-HPP under high pressure conditions up to 250 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…To sum up, besides site-directed mutagenesis, temperature and substrate concentration were shown as parameters affecting the enantioselectivity of BFD. Recently, Berheide et al (2010) has showed that hydrostatic pressure is also able to influence the BFD-catalyzed asymmetric C-C bond formations.…”
Section: Introductionmentioning
confidence: 99%